Conversion of Coal-Fired Power Plants to Cogeneration and Combined-Cycle Thermal and Economic Effectiveness - Bartnik, Ryszard; Buryn, Zbigniew (Springer London : Imprint: Springer, 2011)
Conversion of Coal-Fired Power Plant to Cogeneration and Combined-Cycle presents the methodology, calculation procedures and tools used to support enterprise planning for adapting power stations to cogeneration and combined-cycle forms. The authors analyze the optimum selection of the structure of heat exchangers in a 370 MW power block, the structure of heat recovery steam generators and gas turbines. Conversion of Coal-Fired Power Plant to Cogeneration and Combined-Cycle also addresses the problems of converting existing power plants to dual-fuel gas-steam combined-cycle technologies coupled with parallel systems. Conversion of Coal-Fired Power Plant to Cogeneration and Combined-Cycle is an informative monograph written for researchers, postgraduate students and policy makers in power engineering.